Drinking Water Quality Assessment in Selected Areas of Rawalpindi by Physico-Chemical and Biological Parameters - Asma Jamil,; Amna Haq,; Asadullah,; Hadia Shuja Malik, (International Journal of Economic and Environmental Geology, 2025)
: In this study drinking water quality of some densely populated areas of Rawalpindi was analysed. The main sources of water in the area are water filtration plants and bore tap waters. As water demand has exceeded the supply, many locals have installed bores in order to meet their water needs. The purpose of this study was to determine the quality of drinking water, and to determine whether it is related to gastrointestinal diseases. For this study, water samples were collected from filtration plants, and tap water. Both physicochemical and microbiological parameters play role in determining water quality. Hence, the pH, EC, Salts, TDS, Turbidity, Total Alkalinity, Total Hardness, Total Chloride, Calcium, Magnesium, Sodium, Carbonates, Arsenic, and microbiological parameters like salmonella, and shigella, E. coli and total coliform were analysed by standard procedures. The results showed all the parameters were within the permissible limits, except for EC and TDS, indicating that ions are present in greater amounts in water samples. In case of microbiological parameters, growth of salmonella and shigella, as well as E. coli was found, and permissible limit for total coliforms exceeded in few samples suggesting that water from these sources is contaminated and not fit for use. In comparison, tap water samples were found more contaminated with bacteria as compared to samples from filter plants. Keywords: Drinking water quality, physico-chemical parameters, gastrointestinal diseases, microbiological analysis, arsenic.